Estudo preliminar sobre a liberdade de expressão na perspectiva dos marcos regulatórios das mídias sociais - Bezerra, Isabella Alves (2024)
This dissertation examines the complex and dynamic intersection between disinformation and freedom of expression in the context of social media, which have become central arenas for the formation of public discourse. The study also proposes a critical analysis aiming to understand how Brazilian and foreign legislation present their regulations on content moderation with a view to combating misinformation and the context of dark interests that involve large social media companies. The methodology used is qualitative, and uses theoretical review and documentary research to build a theoretical framework based on the ideas of different authors on the topic, in addition to presenting a comparative study between current social media regulations. It is concluded that there must be a necessary balance involving the critical education of citizens, clear, objective and transparent rules provided by social media and legislation that regulates these tools, whose operation is based on profit to the detriment of any protection that can be established for citizens who use them.